Transcriptional Reprogramming of Pea Leaves at Early Reproductive Stages - Gallardo, Karine; Besson, Alicia; Klein, Anthony; Le Signor, Christine; Aubert, Grégoire; Henriet, Charlotte; Térézol, Morgane; Pateyron, Stéphanie; Sanchez, Myriam; Trouverie, Jacques; Avice, Jean-Christophe; Larmure, Annabelle; et al. (Frontiers in Plant Science, 2019)
Grain legumes, such as pea (Pisum sativum L.), are an important source of dietary proteins. By contributing to the accumulation of seed proteins, nitrogen remobilization from leaves is a pivotal determinant of protein yields. The aim of this study was to unveil the molecular mechanisms underlying this recycling in pea before leaf senescence characterized by chlorophyll breakdown. A time-series analysis of 15N translocation from flowering to maturity distinguished leaves acting mainly as sink or source of nitrogen in different nitrate availability conditions. Leaves differing in their source-sink status were analyzed by transcriptomics and a gene co-expression network predicted regulatory relationships among genes. This revealed distinct and shared molecular features of the two leaf types. The most prominent shared transcriptional regulations were related to cell wall metabolism, which was down-regulated 14 days after flowering in both sink and source leaves. This period was associated with extensive transcriptome changes in sink leaves. Among the set of genes highly up-regulated in sink leaves were genes encoding transporters of nutrients, and particularly of sulfate that may play a role in preventing senescence. A number of transcription factors were also identified as potential regulators of the sink-source transition in pea leaves. Furthermore, candidate genes for switching the metabolism of leaves towards senescence 27 days after flowering were identified, some of which are related to ribosomal RNA processing, autophagy and nitrogen transport. The same approach was conducted in Medicago truncatula to identify shared regulations in this wild legume species. Altogether the results unveil a global view of transcriptional events related to early nutrient remobilization in leaves of legumes and provide a valuable resource of candidate genes that could be targeted by reverse genetics to improve nutrient remobilization and/or delay catabolic processes associated with senescence.